An Analysis of Students’ Creative Thinking Errors in Solving Polyhedra Problems - Erma Jumariah; Husni Sabil; Ranisa Junita (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2025)
Creative thinking skills are important in mathematics learning, especially in geometry, which requires students to generate ideas, choose alternative strategies, and construct flexible representations of spatial figures. However, students' creative abilities in polyhedra are still relatively low. This study aims to describe junior high school students' creative thinking errors in solving problems on flat-sided spatial figures based on indicators of fluency, flexibility, and originality. This study employed a qualitative descriptive approach. Initially, 35 ninth-grade students completed a creative thinking test on polyhedra problems, and three ninth-grade students who exhibited the highest number of errors were selected through purposive sampling for in-depth analysis. The research instrument was a creative thinking skill essay test with open-ended questions about polyhedra. The results showed that students' creative thinking abilities were in the low category, with fluency scores of 38%, flexibility scores of 32.5%, and originality scores of 21.7%. Qualitatively, students tended to produce similar container shapes, explored few variations in shape, and showed few truly new ideas. Students made mistakes in providing ideas, incorrectly converted information into solid elements, and wrote answers that could not be realized as three dimensional solids. Overall, the study concludes that students’ creative thinking skills in solving polyhedra problems still require enhancement through learning strategies that promote idea exploration and foster a deeper understanding of polyhedral concepts.